Bahasa Indonesia Dalam Dunia Pendidikan dan Tantangan Dalam Penggunaannya Secara Akademik - Nasution, Abidah Ramadhani; Pulungan, Hendra Kurnia; Marsyah, Aralia Putri; Dewi, Artika Sardiana; Sari, Defi Mawar; Pangaribuan, Devy J.R; Manurung, Elisabet Magdalena; Sinaga, Husna Khoiri; Harefa, Rili Angelica; Hutasoit, Sartika Br (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article examines the role of the Indonesian language in the national education context and analyzes various challenges in its use as an academic language. Through a descriptive qualitative approach by interviewing three language and education experts, this research identifies several main challenges such as limitations in technical vocabulary, foreign language influence, and gaps between standard Indonesian and everyday language. The results show that systematic efforts are needed to strengthen the position of Indonesian as a scientific language, including standardization of academic terms, development of quality teaching materials, and improvement of scientific writing skills among academics. In conclusion, strengthening Indonesian in the academic domain requires collaboration between language institutions, educational institutions, and the academic community to ensure its sustainability as a language of science in the era of globalization.